The Race for ACE: Targeting Angiotensin-Converting Enzymes (ACE) in SARS-CoV-2 Infection - Schieffer, Elisabeth; Schieffer, Bernhard (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
The SARS-CoV-2 virus is spreading around the world, and its clinical manifestation COVID-19 is challenging medical, economic, and social systems. With more and more scientific and social media reports on the COVID-19 pandemic appearing, differences in geographical presentations and clinical management occur. Since ACE2 (angiotensin-converting enzyme 2) is the gatekeeper receptor for the SARS-CoV-2 virus in the upper bronchial system, we here focus on the central role of the renin-angiotensin aldosterone system (RAAS) in the SARS-CoV-2 virus infection, the role of pharmacological RAAS inhibitors, and specific genetic aspects, i.e., single nucleotide polymorphisms (SNP) for the clinical outcome of COVID-19. We aimed to bring together clinical, epidemiological, molecular, and pathophysiological and pharmacological data/observations on cardiovascular aspects in the actual SARS-CoV-2 virus pandemic. In detail, we will report controversies about the Yin-Yan between ACE2 and ACE1 and potential implications for the treatment of hypertension, coronary artery disease, and heart failure. Here, we summarize the encouraging and dynamic global effort of multiple biomedical disciplines resulted in astonishing fight against COVID-19 targeting the renin-angiotensin-aldosterone system, yet the race for ACE just begun.